Стихи: поэзия / В. Д. Берестов [и др.] - Берестов Валентин Дмитриевич (Хрестоматия. Начальная школа, 2008)
Экземпляры: (20211108) / Инвентарный номер: 3500 / Цена: / Авт.знак: С 80 / ББК: 84(2Рос=Рус)6